Analysis in Differences Concept of Setting on Tukang Ojek Pengkolan and Amanah Wali 6 Series - Fazriah, Tisha Maulida; Nafsika, Salsa Solli (Cinematology: Journal Anthology of Film and Television Studies, 2023)
Tukang Ojek Pengkolan and Amanah Wali 6 is a series that aired on RCTI Channel. Setting became the main highlight in this research, literature study, content analysis study, and comparative study became a reference in the author's research. There are some interesting differences between the two selected series. From the results of the analysis, the creative team is very influential in the success of a drama Series or film. If not creative, then the image of the series itself failed to awaken. The style of dress is also the main highlight of society, especially in the mise-en-scene. If the style of dress does not match the storyline, it can be said that it has not been successful, because clothes can also build a culture in films starring each of the players. Not only that, speaking style of dress can also be a medium of communication and messages for the wearer. In this context, the clothing of one of them is influential for the audience because it is the first part that is seen before the character's acting skills. Then the role of an art system is needed, because it must be able to direct the viewer to the plot that has been established by the writer and director. Both series are intelligent in choosing locations, although there are quite noticeable differences between the creation of sets and the utilization of existing sets. The details of the property are arranged equally impressively, the setting is made in such a way that it resembles the original setting. As in the Amanah Wali 6 Series, even though they are in the basement, they present the property as if juggling the contents of the room into a market and housing. It becomes an innovation so that the fictitious impression looks more real.